O eu e o outro: fraturações sociais na fantasia Porém bruxa de Carol Chiovatto - Sbardelini, Rodrigo dos Santos (2024)
The dissertation seeks to analyze how Carol Chiovatto's work Porém Bruxa (2022a) uses elements of fantasy literature to address the fractures of contemporary social life. To do so, we revisit theoretical reflections on the concepts of the "fantastic," "fantasy," and their differences (Todorov, year; Roas, 2013; and Gama-Khalil, 2013). In dialogue with Mendlesohn (2008), we situate Chiovatto's work within the urban fantasy subgenre, characterized by magical and supernatural elements that interact with a contemporary urban reality. Our focus then shifts to how a fantasy work addresses social issues, the construction of the "self" through the "other," and the fractures of themes such as violence and the abuse of power. To understand the intersections between literature and society, we draw on authors such as Antonio Candido (1976), Flora Süssekind (2005), and Regina Dalcastagnè (2012), particularly concerning urbanization and spatial segregation, highlighted as crucial elements in shaping contemporary narratives. Finally, we also examine the witch as a marginalized character who questions and subverts established norms. Ultimately, we aim to demonstrate that, in a work like Chiovatto's, fantasy literature becomes a provocative vehicle for discussing and questioning social and cultural norms